2006
DOI: 10.1038/sj.ijo.0803311
|View full text |Cite
|
Sign up to set email alerts
|

Childhood overweight and elementary school outcomes

Abstract: Objective: To examine the link between childhood overweight status and elementary school outcomes. Design: Prospective study design: multivariate regression models examining the association between changes in overweight status and school outcomes between kindergarten entry and end of third grade, after controlling for various child, family and school characteristics. Subjects: Nationally representative sample of US children who entered kindergarten in 1998, with longitudinal data on body mass index (BMI) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
253
10
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(295 citation statements)
references
References 32 publications
20
253
10
12
Order By: Relevance
“…46 In community samples of children and adolescents, an association between overweight and obesity and lower academic competencies has repeatedly been observed. [6][7][8] In concordance to those studies, a higher likelihood of low academic competencies would have been expected in this clinical sample of obese children as compared to the general population of Icelandic children. As no other studies of academic competencies among obese children in a clinical sample were found, these findings require replication.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…46 In community samples of children and adolescents, an association between overweight and obesity and lower academic competencies has repeatedly been observed. [6][7][8] In concordance to those studies, a higher likelihood of low academic competencies would have been expected in this clinical sample of obese children as compared to the general population of Icelandic children. As no other studies of academic competencies among obese children in a clinical sample were found, these findings require replication.…”
Section: Discussionsupporting
confidence: 61%
“…[1][2][3][4][5] In community samples of children and adolescents, overweight and obesity has also been associated with lower academic competencies, [6][7][8] although this association has, to our knowledge, not been studied in a clinical sample of obese children.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…7,8 Findings from population-based studies do suggest that associations between obesity and impairment in children's psycho-social functioning may be mediated by age and gender, with greater impairment in older children and in females. 7,10 Few studies have addressed the possible effects of childhood obesity on other aspects of developmental functioning. A recent study of first-grade children in Germany (mean age ¼ 6.7 years) 11 found that obesity was associated with impairment in motor development in both boys and girls, whereas Datar and Sturm (2004), 12 in a large and nationally representative sample children beginning kindergarten in the US, found that obesity was associated with higher levels of teacher-and parent-reported behavior problems in girls, but not boys, after controlling for socio-demographic, lifestyle and family variables.…”
Section: Introductionmentioning
confidence: 99%
“…15 Impairment in developmental functioning during childhood may have adverse effects on self-esteem, psycho-social functioning more generally, and academic performance, as well as increasing the risk of obesity later in life. 10,12 To date, the vast majority of studies that have examined associations between childhood overweight and impairment in specific aspects of functioning have been conducted in adolescents. Hence, where associations have been observed, it is unclear whether these effects were apparent earlier in the child's development and, if so, at what point.…”
Section: Introductionmentioning
confidence: 99%